Examining the phase evolution of lithium disilicate glass‐ceramics with lithium tantalate as a secondary phase. Issue 1 (14th September 2021) - DeCeanne, Anthony V.; Fry, Aubrey L.; Wilkinson, Collin J.; Dittmer, Marc; Ritzberger, Christian; Rampf, Markus; Mauro, John C.
Abstract: Lithium disilicate glass‐ceramics were discovered in the 1950s, and the evolution of the main target phase of these materials is well known. However, the lithium disilicate system is still an area of active research, especially when a secondary phase is introduced since the phase evolution of secondary phases is not currently understood. The present study examines the main target phases, as well as a secondary phase of lithium tantalate, via X‐ray diffraction. A large data set is obtained to investigate the evolution of all phases. It is found that the nucleation of the precursor lithium metasilicate phase is coupled to both the nucleation of the primary target phase, lithium disilicate, and the nucleation of lithium tantalate. A reaction equation describing this relationship is proposed.